Partial Substitution of Cadmium and its Effect on the Electrical Properties of the Superconducting System (YBCO) - Zainab Amer ALbawiy; Haider MJ. Haider (Genius Journals, 2023)
In this work, the effect of partial substitution of Cadmium (Cd) instead of Copper (Cu) on the electrical properties of the compound (YBa2Cu3-xCdxO6+δ) was studied, where Cadmium fills the spaces between the granule cells. The compound was prepared using the state reaction method. Solid (SSR) with replacement ratios (x=0,0.1,0.2, and 0.3) The results were analyzed by conducting X-ray diffraction (XRD) examination to find the lattice constants and to know the crystal structure of the samples, so all samples showed a specific behavior based. As the electrical resistivity was studied as a function of the critical temperature, it was found that all samples showed superconductivity behavior, and the optimal sample was at the replacement ratio (X = 0.3), where the highest critical temperature was recorded (K 101.3Tc (offset=)( and the highest energy gap where the highest recorded Its value is (Eg = 0.030842051ev).
Keywords: partial substitution of the elements; yttrium; YBCO; superconductivity